2020
DOI: 10.21203/rs.3.rs-49936/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Impact of COVID-19 Pandemic on Cardiac Surgery in Israel

Abstract: Background: Ever since the coronavirus disease 2019 (COVID-19) has become a pandemic, worldwide efforts are being made to “flatten the curve”. Israel was amongst the first countries to impose significant restrictions. As a result, cardiac surgeons have been required to scale down their routine practice, resulting in a significant reduction in the number of cardiac surgeries. The aim of this study is to characterize the impact of COVID-19 on cardiac surgery in Israel. Methods: This is a retrospective observatio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 5 publications
0
8
2
1
Order By: Relevance
“…2 Internal Medicine Wing, Sheba Medical Center, Tel Hashomer, Israel Affiliated To Sackler Faculty of Medicine, Tel-Aviv University, Tel Aviv, Israel. 3 Israel Defense Forces, Israel Medical Corps, Ramat Gan, Israel.…”
Section: Fundingmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Internal Medicine Wing, Sheba Medical Center, Tel Hashomer, Israel Affiliated To Sackler Faculty of Medicine, Tel-Aviv University, Tel Aviv, Israel. 3 Israel Defense Forces, Israel Medical Corps, Ramat Gan, Israel.…”
Section: Fundingmentioning
confidence: 99%
“…In Israel, there was a significant decline in the visits to the emergency department (ED) during the first wave of the Covid-19 outbreak [2]. Hospital occupancies decreased and the number of elective procedures including cardiac surgeries declined [1][2][3]. Mendlovic et al showed a decrease in the number of patients visiting the ED and in the number of admissions to medical wards during the outbreak.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, due to the initial severe gap of knowledge (unknown level of virus penetration, scarcity of swab test and PPE, unclear healthcare protection protocols) therapeutic approach for cardiac urgencies was less than empirical, with uncertain organization and dismal outcomes. At nearly one year from COVID outbreak, few data (almost only case/centers experience) have been published so far on the impact of COVID‐19 on surgically treated patients 15,16 . However, the impact of health system rearrangement, human and physical resources allocation, and viremia‐related thromboembolic and respiratory burden on complex surgical outcomes is mandatory for safe surgical activity restart.…”
Section: Discussionmentioning
confidence: 99%
“…14 F I G U R E 1 ROC curve: predictivity of age for higher in-hospital mortality; AUC, area under curve; confidence limits are plotted (blue area); ROC, receiver operating characteristic (almost only case/centers experience) have been published so far on the impact of COVID-19 on surgically treated patients. 15,16 However, the impact of health system rearrangement, human and physical resources allocation, and viremia-related thromboembolic and respiratory burden on complex surgical outcomes is mandatory for safe surgical activity restart.…”
Section: Covid Subgroupmentioning
confidence: 99%
“…To contain the spread of the virus and ease the burden on hospitals, strict measures unprecedented in modern times were imposed. Entire nations have been placed under lockdown, schools and businesses closed and travel was restricted [ 5 , 6 ]. In Austria, these measures against COVID-19 became obligatory on 16 March 2020.…”
Section: Introductionmentioning
confidence: 99%